2020
DOI: 10.4236/ijcm.2020.1110049
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Kidney Stones and Salivary Uric Acid on Dental Calculus Formation and Periodontal Status among Some Saudi Patients Aged 25 - 70 Years

Abstract: Background: The formation of kidney stones is considered a complicated process. Consequently, there are many questions about the link between kidney stones formation and level of salivary uric acid and calculus formation on the teeth surfaces. Objectives: To evaluate the correlation between the level of salivary uric acid and kidney stones formation and their influence on dental calculus and periodontal status among Saudi patients aged 25-70 years. Materials and Methods: 120 Saudi male patients were examined (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
1
1
Order By: Relevance
“…The present study demonstrated a positive correlation between the calculus index and the plaque index for the control and kidney stone groups. This is in agreement with previous studies that found a positive correlation between the value of plaque index and calculus formation [13,14].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study demonstrated a positive correlation between the calculus index and the plaque index for the control and kidney stone groups. This is in agreement with previous studies that found a positive correlation between the value of plaque index and calculus formation [13,14].…”
Section: Discussionsupporting
confidence: 94%
“…This condition, which is not related to the frequency of the dental calculi, may be directly related to oral hygiene status. This contradicts other studies, which suggested that the formation of dental calculus may be an indicator of other types of stones, such as kidney stones [11,13]. Although caution must be used in interpreting the results due to the small sample size, these findings suggest that the formation of dental plaque and calculus may not predict the development of kidney stones.…”
Section: Discussioncontrasting
confidence: 77%
“…These natural substances can be considered as adjuncts to conventional therapy for periodontitis. However, studies on the relationship between antioxidant status and periodontitis have produced discordant results [111][112][113]: not all studies have observed significant differences in total antioxidant levels between saliva samples from healthy subjects and those with periodontitis. This study aims to further investigate the role of sulfhydryl groups (thiols) in the periodontal environment by exploring their variations in the initial and clinical manifestations of periodontal disease [7,114].…”
Section: Introductionmentioning
confidence: 99%